2011
DOI: 10.1002/ca.21198
|View full text |Cite
|
Sign up to set email alerts
|

Osseous microarchitecture of the scaphoid: Cadaveric study of regional variations and clinical implications

Abstract: Bone strength and structure are closely associated with fracture and screw fixation, however osseous micro architecture on scaphoid has not been clearly addressed. We conducted histomorphometric study of the scaphoid using micro CT to find regional variations and differences in the scaphoid to provide better understanding of fracture mechanism and suggest optimal screw position. We divided scaphoid into eight regions and collected regional data from eleven different cadaveric scaphoids. A computer program was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Interestingly, this zone corresponded to the mid-portion of the scaphoid where the centre of the waist is located. Su-Bum et al [37] found in CT scans of 20 male scaphoids the highest bone density parameters at regions that articulate with the radius and the capitate. The low bone density at the centre combined with the narrow anatomical shape of the waist explains the frequency of fractures at this site which is approximately 75% of all scaphoid fractures [3].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, this zone corresponded to the mid-portion of the scaphoid where the centre of the waist is located. Su-Bum et al [37] found in CT scans of 20 male scaphoids the highest bone density parameters at regions that articulate with the radius and the capitate. The low bone density at the centre combined with the narrow anatomical shape of the waist explains the frequency of fractures at this site which is approximately 75% of all scaphoid fractures [3].…”
Section: Discussionmentioning
confidence: 98%
“…However, extremity length was not taken into account in the previous HR-pQCT studies in adults with OI, and the effects of bone deformities on scan region were not discussed. Also, trabecular void spaces have been noted on HR-pQCT in OI [62], but their influence on HR-pQCT parameters has not been described. Evaluation of the feasibility of using HR-pQCT in OI is limited to a small study in nine children with OI [64].…”
Section: First-generation Hr-pqct Second-generation Hr-pqct Standard ...mentioning
confidence: 99%
“…Additionally, it may, as a single parameter, not fully describe the complexity and heterogeneity of OI. HR-pQCT has recently been used to investigate bone microarchitecture in adults with OI as compared to non-OI populations [61][62][63], but the small sample sizes in these studies may not have fully captured the heterogeneity in OI. Furthermore, difficulties may potentially be faced when using HR-pQCT in OI, which were not addressed in these studies.…”
Section: First-generation Hr-pqct Second-generation Hr-pqct Standard ...mentioning
confidence: 99%
See 1 more Smart Citation